2008
DOI: 10.1038/ncpneuro0853
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of bulbar symptoms in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is the most common neurodegenerative disease of the motor system. Bulbar symptoms such as dysphagia and dysarthria are frequent features of ALS and can result in reductions in life expectancy and quality of life. These dysfunctions are assessed by clinical examination and by use of instrumented methods such as fiberendoscopic evaluation of swallowing and videofluoroscopy. Laryngospasm, another well-known complication of ALS, commonly comes to light during intubation and extu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
152
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(164 citation statements)
references
References 58 publications
2
152
0
10
Order By: Relevance
“…Zudem ist die Dysphagie ein dominantes klinisches Merkmal bei verschiedenen neuromuskulären Erkrankungen. So finden sich bei bis zu 30% der Patienten mit amyotropher Lateralsklerose bereits zum Zeitpunkt der Diagnosestellung Beeinträchtigungen des Schluckaktes [15], während im weiteren Krankheitsverlauf nahezu alle Patienten eine Dysphagie entwickeln. Auch Patienten mit entzünd-lichen Muskelerkrankungen leiden häu-fig unter Schluckstörungen.…”
Section: Primäre Und Sekundäre Presbyphagieunclassified
“…Zudem ist die Dysphagie ein dominantes klinisches Merkmal bei verschiedenen neuromuskulären Erkrankungen. So finden sich bei bis zu 30% der Patienten mit amyotropher Lateralsklerose bereits zum Zeitpunkt der Diagnosestellung Beeinträchtigungen des Schluckaktes [15], während im weiteren Krankheitsverlauf nahezu alle Patienten eine Dysphagie entwickeln. Auch Patienten mit entzünd-lichen Muskelerkrankungen leiden häu-fig unter Schluckstörungen.…”
Section: Primäre Und Sekundäre Presbyphagieunclassified
“…The following information was obtained from medical records: duration to initiation of gastronomy feeding from disease onset (initiation of gastronomy feeding was defined as the time of combination of oral intake and gastronomy feeding due to dysphagia), dysphagia onset (duration to emerging dysphagia from disease onset; dysphagia symptoms include increased eating time, coughing or throat clearing, gurgly voice, and food remnants in the mouth (Kühnlein et al 2008, Logemann et al 2009)), course of dysphagia (duration to initiation of gastronomy feeding from dysphagia onset), and course of respiratory function after dysphagia onset (duration to intervention with noninvasive ventilation (NIV) or tracheostomy invasive ventilation (TIV) from dysphagia onset; all patients were treated with NIV when FVC dropped <50%, at the onset of dyspnea, if NIV was unsuccessful, TIV was performed immediately)…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Strand et al reported that patients with ALS who have early eating problems, should be advised of the need for dietary modification, which is required for the continuation of oral intake (Strand et al 1996). Dietary modification has been shown to be an effective approach for moderate dysphagia (Kühnlein et al 2008). Furthermore, with compensatory swallowing strategies such as the supraglottic swallow and posture positioning, the ability to swallow safely Issue 3 Copyright © 2015, Knowledge Enterprises Incorporated.…”
Section: Course Of Dysphagia In Alsmentioning
confidence: 99%
“…23 We need a more accurate way to detect and quantify the level of bulbar involvement. 24,25 A specific test of bulbar function may help to recognize the group of patients at higher risk of NIV failure, at need for early initiation of mechanical cough assistance, or will simply help to better classify/quantify bulbar involvement. 26 An alternative or complementary option to NIV for the support of inspiratory function is available.…”
Section: See the Original Studies On Pages 1424 And 1433mentioning
confidence: 99%